Neolignans and flavonol glycosides from the leaves of Viburnum lutescens Blume - Duc Thien, Le; Thi Dung, Duong; Phuong Minh, Nguyen; Hai Dang, Nguyen (Vietnam Journal of Science and Technology, 2022)
Four neolignans, (7S,8S)-dihydrodehydrodiconiferyl alcohol 9-O-β-D-glucopyranoside (1), (7S,8S)-dihydrodehydrodiconiferyl alcohol 9′-O-β-D-glucopyranoside (2), (7S,8R)-5-methoxydihydrodehydrodiconiferyl alcohol 4-O-β-D-glucopyranoside (3), and (7S,8R)-5-methoxydihydrodehydrodiconiferyl alcohol 9′-O-β-D-glucopyranoside (4) and five flavonol glycosides, kaempferol-3-O-β-D-glucopyranoside (5), kaempferol 3-O-rutinoside (6), kaempferol 3-O-α-L-rhamnopyranosyl (1→6)-β-D-galactopyranoside (7), kaempferol 3-O-β-D-galactopyranoside (8), and quercetin 3-O-β-D-glucopyranoside (9) were isolated from the methanol extract of Viburnum lutescens Blume leaves. Their chemical structures were elucidated by 1D- and 2D-NMR spectra and comparison with those reported in the literature. Compounds 1, 2, and 4 were reported from Viburnum genus for the first time